Prognosis of hepatitis B virus reactivation in newly diagnosed multiple myeloma in modern era therapy: a retrospective study - Lv, Weiran; Li, Xiaojin; Xu, Jingbo; Wang, Yun; Huang, Hanying; Hu, Fang; Cui, Yingying; Song, Yuanbin; Chen, Lezong; Wu, Bingyi; Liang, Yang (PeerJ (San Francisco, CA), 2024)
Studies on the prognosis of hepatitis B virus (HBV) reactivation following modern therapies for newly diagnosed MM (NDMM) are lacking. In this retrospective study, we aimed to assess the incidence, risk factors and prognosis of HBV reactivation in NDMM. A total of 33 of 355 patients with NDMM and HBV reactivation were included in this study. Multivariable analysis showed that hepatitis B surface antigen-positivity, hepatitis B core antibody-positivity, bortezomib-containing regimens, autologous stem cell transplantation, and gain of 1q21 were identified as independent risk factors of HBV reactivation in NDMM patients. The NDMM patients with HBV reactivation had poorer 3-year overall survival (OS) and progression-free survival (PFS) than did those without HBV reactivation, as confirmed by multivariate analysis. In conclusion, HBV reactivation in patients with NDMM constitutes a significant complication, correlating with reduced OS and PFS, and emerges as a potential adverse prognostic factor in the contemporary era of treatment.